2015
DOI: 10.1021/acs.jced.5b00577
|View full text |Cite
|
Sign up to set email alerts
|

Stokes–Einstein–Nernst Relation in Dilute Electrolyte Solutions of Lithium Perchlorate in Polyethylene Glycols (200, 300, 400, and 600)

Abstract: The electrical conductivity was measured for dilute electrolyte solutions of lithium perchlorate (LiClO 4 ) in polyethylene glycols (PEG) of different molecular weights (200−600). The results were interpreted in the frame of the Stokes−Einstein−Nernst model. It was found (i) a breakdown of the model in the glycol-based polymeric matrices used and (ii) an increase of the deviation from the model predictions with increasing molecular weight of the matrix. The role of the flexibility of HO− [CH 2 −CH 2 −O] n −H c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 17 publications
(25 reference statements)
2
15
0
Order By: Relevance
“…The ε′ values of 1 MHz are taken as the static permittivity ε s (T) of liquid PEG200, and these are given in Table 1. These ε s (T) values of the neat PEG200 are found in good agreement with that of the molecular sieve dried PEG200 [8], which confirms that the concentration of unidentified ionic contaminants does not affect the static permittivity of neat liquid PEG200, and it is also true in case of Li + ClO 4 − diluted electrolyte solution of PEGs solvent [8]. Low-frequency dielectric spectroscopic studies on different static permittivity dipolar liquids (solvents) have confirmed that their ε s values are independent of ions contaminants, but the high frequency value at which steady state in ε′(f) spectrum appeared depends on the ions concentration [16,17,20].…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…The ε′ values of 1 MHz are taken as the static permittivity ε s (T) of liquid PEG200, and these are given in Table 1. These ε s (T) values of the neat PEG200 are found in good agreement with that of the molecular sieve dried PEG200 [8], which confirms that the concentration of unidentified ionic contaminants does not affect the static permittivity of neat liquid PEG200, and it is also true in case of Li + ClO 4 − diluted electrolyte solution of PEGs solvent [8]. Low-frequency dielectric spectroscopic studies on different static permittivity dipolar liquids (solvents) have confirmed that their ε s values are independent of ions contaminants, but the high frequency value at which steady state in ε′(f) spectrum appeared depends on the ions concentration [16,17,20].…”
Section: Resultssupporting
confidence: 78%
“…For the liquid dielectric materials of Ohmic behaviour, their dielectric loss ε″(f) spectrum presents itself, according to straight line relation ε″(f) = σ dc /2πfε 0 , where σ dc is the direct current (dc) ionic conductivity [17][18][19][20]. This behaviour is also true for the diluted electrolyte solutions [8]. Further, Fig.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations